Preparation method of zinc sulfide substrate infrared medium wave antireflection film system
The six-layer film structure composed of Ge, Al2O3, YF3 and Y2O3 film materials solves the problems of low transmittance and high film stress of zinc sulfide-based infrared anti-reflection film in the 3-5μm band, and realizes a film system with high transmittance, low stress and high stability that can adapt to various environments.
Patent Information
- Application Number
- CN202510787912.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-09-12
AI Technical Summary
The existing zinc sulfide-based infrared anti-reflection film has low transmittance in the 3-5μm band, and has problems such as high film stress and easy cracking and falling off, which affects stability and reliability.
The Sub (zinc sulfide substrate)/Ge/Al2O3/Ge/Al2O3/YF3/Y2O3/Air structure composed of four film materials: Ge, Al2O3, YF3 and Y2O3. Six film layers are formed by ion source assisted deposition. Two layers of Ge and two layers of Al2O3 serve as transition layers, and Y2O3 serves as a protective layer to reduce stress and improve adhesion.
The average transmittance of the zinc sulfide substrate in the 3-5μm band is increased to more than 98%, the stress of the film layer is reduced, cracking and falling off are avoided, the stability and reliability are enhanced, and the environmental adaptability is improved.
Smart Images

Figure CN120624987A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of optical thin films, and in particular to a method for preparing a zinc sulfide-based infrared mid-wave antireflection film system. Background Art
[0002] Zinc sulfide (ZnS) is an important infrared optical material with high transmittance in the mid-wave infrared (3-5μm) band. It is widely used in thermal imaging, infrared detection, and other fields. However, due to the large refractive index difference between ZnS and air, its surface experiences high reflection losses, reducing the transmission efficiency of optical systems. To reduce reflection losses and improve optical system performance, an antireflection coating is typically applied to the ZnS substrate.
[0003] Traditional zinc sulfide antireflection coatings mostly use a single layer of magnesium fluoride (MgF2) film or a double layer film system consisting of zinc sulfide (ZnS) and yttrium fluoride (YF3). However, these film systems have the following shortcomings:
[0004] Single-layer MgF2 film: Although the preparation process is simple, its anti-reflection effect in the 3-5μm band is limited, and the average transmittance is usually less than 97%.
[0005] ZnS / YF3 double-layer film: Although the anti-reflection effect is better than that of a single-layer MgF2 film, the stress between the film layers is large, which can easily lead to problems such as film cracking and falling off, affecting the stability and reliability of the film system. Summary of the Invention
[0006] In view of the problems existing in the background technology, an object of the present disclosure is to provide a method for preparing a zinc sulfide-based infrared mid-wave anti-reflection film system, which can improve the average transmittance in the 3-5 μm band.
[0007] Another object of the present disclosure is to provide a method for preparing a zinc sulfide-based infrared mid-wave anti-reflection film system, which can effectively reduce the stress between film layers.
[0008] Another object of the present disclosure is to provide a method for preparing a zinc sulfide-based infrared mid-wave anti-reflection film system, which can avoid the risk of the film system falling off and improve the stability and reliability of the film system.
[0009] Another object of the present disclosure is to provide a method for preparing a zinc sulfide-based infrared mid-wave anti-reflection film system, which can improve the environmental stability of the film system.
[0010] Therefore, a method for preparing a zinc sulfide-based infrared medium-wave anti-reflection film system includes the following steps: S1, before plating, cleaning the accompanying plating sheet and product of the zinc sulfide substrate serving as the lens and preparing four film materials: Ge, Al2O3, YF3 and Y2O3; S2, placing the cleaned lens into a fixture, hanging the fixture with the lens in place into the cavity of a coating machine, vacuum baking and pre-melting the film materials; S3, cleaning the lens with an ion source; S4, sequentially plating a first Ge film layer, a second Al2O3 film layer, a third Ge film layer, a fourth Al2O3 film layer, a fifth YF3 film layer and a sixth Y2O3 film layer on the first surface of the lens under vacuum conditions, the six film layers constituting the film system, and all six film layers are deposited using an ion source as an aid; S5, maintaining a constant temperature after plating; S6, cooling and removing the component; S7, repeating steps S1 to S6 to coat the same film system on the second surface of the lens.
[0011] The beneficial effects of the present disclosure are as follows.
[0012] In the disclosed method for preparing a zinc sulfide-based mid-wave infrared anti-reflection coating, step S4 results in a coating structure on each surface of the lens comprising four materials: Ge, Al2O3, YF3, and Y2O3: Sub(zinc sulfide substrate) / Ge / Al2O3 / Ge / Al2O3 / YF3 / Y2O3 / Air. This results in the zinc sulfide substrate and the coating system on both surfaces having a high average transmittance in the 3-5 μm band, effectively improving the average transmittance in the 3-5 μm band. As verified by testing, the average transmittance of the zinc sulfide substrate and the coating system on both surfaces in the 3-5 μm band exceeds 98%.
[0013] In the disclosed method for preparing a zinc sulfide-based infrared mid-wave anti-reflection film system, through step S4, the film system structure on each surface of the lens is a structure of Sub(zinc sulfide substrate) / Ge / Al2O3 / Ge / Al2O3 / YF3 / Y2O3 / Air (air), composed of four film materials: Ge, Al2O3, YF3, and Y2O3. The two Ge film layers and the two Al2O3 film layers serve as transition layers, effectively reducing the stress between the film layers (i.e., providing low stress). This avoids the problems of cracking and shedding caused by excessive stress in conventional film systems in the background art, thereby improving the stability and reliability of the film system. In addition, the Ge film layer is used to connect the zinc sulfide substrate and the film system, significantly improving the adhesion between the zinc sulfide substrate and the film system, avoiding the risk of film shedding and improving the stability and reliability of the film system.
[0014] In the disclosed method for preparing a zinc sulfide-based infrared medium-wave anti-reflection film system, through step S4, the film system structure on each surface of the lens is Sub (zinc sulfide substrate) / Ge / Al2O3 / Ge / Al2O3 / YF3 / Y2O3 / Air (air) composed of four film materials: Ge, Al2O3, YF3, and Y2O3. Y2O3 serves as the outermost protective layer. It has excellent mechanical strength and chemical stability, and can effectively protect the film system from the influence of the external environment (such as humidity, temperature changes, mechanical friction, etc.). This enables the film system to adapt to various harsh environments, prolongs its service life, and improves the environmental stability of the film system.
[0015] In the method for preparing the infrared medium-wave anti-reflection film system on a zinc sulfide substrate disclosed herein, as verified in the test process, the zinc sulfide substrate together with the film system on both sides can pass a total of seven tests: blister test, adhesion test, moderate friction resistance test, constant temperature and humidity test, high temperature test, low temperature test, and salt spray test.
[0016] The disclosed method for preparing the zinc sulfide-based infrared mid-wave antireflection film system can be widely used in products required in the fields of thermal imaging, infrared detection, laser transmission, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic structural diagram of a substrate and two-sided film systems prepared according to the method for preparing a zinc sulfide substrate infrared mid-wave anti-reflection film system disclosed in the present invention.
[0018] Figure 2 It is a curve diagram of the transmittance of the accompanying coating sheet of Example 1 together with the films coated on both sides in the 3-5 μm band. DETAILED DESCRIPTION
[0019] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which can be implemented in various forms. Therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one skilled in the art to variously implement the present disclosure.
[0020] [Preparation method of zinc sulfide-based infrared mid-wave antireflection film system]
[0021] Reference Figure 1 The method for preparing the zinc sulfide-based infrared mid-wave antireflection film system disclosed herein comprises the following steps:
[0022] S1, before plating, clean the accompanying plating sheet and products of the zinc sulfide substrate used as the lens, and prepare the four film materials of Ge, Al2O3, YF3 and Y2O3;
[0023] S2, the cleaned lens is placed in the fixture, and the fixture with the lens is hung in the cavity of the coating machine, vacuumed and baked, and the film material is pre-melted;
[0024] S3, ion source cleaning lens;
[0025] S4, under vacuum conditions, sequentially depositing a first Ge film layer, a second Al2O3 film layer, a third Ge film layer, a fourth Al2O3 film layer, a fifth YF3 film layer, and a sixth Y2O3 film layer on the first surface of the lens, so that the six film layers constitute a film system, and all six film layers are deposited using an ion source assisted deposition;
[0026] S5, constant temperature maintenance after plating;
[0027] S6, cooling and picking up;
[0028] S7, repeating steps S1 to S6 to coat the same coating system on the second surface of the lens.
[0029] In the disclosed method for preparing a zinc sulfide-based mid-wave infrared anti-reflection coating, step S4 results in a coating structure on each surface of the lens comprising four materials: Ge, Al2O3, YF3, and Y2O3: Sub(zinc sulfide substrate) / Ge / Al2O3 / Ge / Al2O3 / YF3 / Y2O3 / Air. This results in the zinc sulfide substrate and the coating system on both surfaces having a high average transmittance in the 3-5 μm band, effectively improving the average transmittance in the 3-5 μm band. As verified by testing, the average transmittance of the zinc sulfide substrate and the coating system on both surfaces in the 3-5 μm band exceeds 98%.
[0030] In the disclosed method for preparing a zinc sulfide-based infrared mid-wave anti-reflection film system, through step S4, the film system structure on each surface of the lens is a structure of Sub(zinc sulfide substrate) / Ge / Al2O3 / Ge / Al2O3 / YF3 / Y2O3 / Air (air), composed of four film materials: Ge, Al2O3, YF3, and Y2O3. The two Ge film layers and the two Al2O3 film layers serve as transition layers, effectively reducing the stress between the film layers (i.e., providing low stress). This avoids the problems of cracking and shedding caused by excessive stress in conventional film systems in the background art, thereby improving the stability and reliability of the film system. In addition, the Ge film layer is used to connect the zinc sulfide substrate and the film system, significantly improving the adhesion between the zinc sulfide substrate and the film system, avoiding the risk of film shedding and improving the stability and reliability of the film system.
[0031] In the disclosed method for preparing a zinc sulfide-based infrared medium-wave anti-reflection film system, through step S4, the film system structure on each surface of the lens is Sub (zinc sulfide substrate) / Ge / Al2O3 / Ge / Al2O3 / YF3 / Y2O3 / Air (air) composed of four film materials: Ge, Al2O3, YF3, and Y2O3. Y2O3 serves as the outermost protective layer. It has excellent mechanical strength and chemical stability, and can effectively protect the film system from the influence of the external environment (such as humidity, temperature changes, mechanical friction, etc.). This enables the film system to adapt to various harsh environments, prolongs its service life, and improves the environmental stability of the film system.
[0032] In the method for preparing the infrared medium-wave anti-reflection film system on a zinc sulfide substrate disclosed herein, as verified in the test process, the zinc sulfide substrate together with the film system on both sides can pass a total of seven tests: blister test, adhesion test, moderate friction resistance test, constant temperature and humidity test, high temperature test, low temperature test, and salt spray test.
[0033] The disclosed method for preparing the zinc sulfide-based infrared mid-wave antireflection film system can be widely used in products required in the fields of thermal imaging, infrared detection, laser transmission, etc.
[0034] In step S1, for example, ultrasonic cleaning is performed, using an aluminum oxide polishing solution, followed by ultrasonic pure water cleaning. The aluminum oxide polishing solution is a 0.1 μm polycrystalline diamond solution from Nanjing Henry Precision Optics Co., Ltd. Ultrasonic cleaning removes surface contaminants, ensuring cleanliness before coating and preventing impurities from interfering during the coating process, thereby improving the flatness of the film layer.
[0035] In step S1 , for example, the thickness of the accompanying plating sheet is 1.0 mm.
[0036] In step S2, for example, the coating machine is a vacuum coating machine equipped with a Hall ion source manufactured and sold by Chengdu Siwork Vacuum Technology Co., Ltd.
[0037] The pre-melting in step S2 can release the impurities in the film material and change the state of the film material to ensure the smooth progress of the coating process. In one example, in step S2, the temperature of the coating machine cavity is set to 150℃. When the vacuum reaches (3.0-5.0)×10 -3 The film materials are pre-melted at Pa. Ge film materials, Al2O3 film materials and YF3 film materials are pre-melted, while Y2O3 film materials are not pre-melted. Ge film materials and Al2O3 film materials are pre-melted by electron beam heating, and YF3 film materials are pre-melted by resistance heating. After the film materials are pre-melted, the temperature of the cavity of the coating machine reaches 150℃ and is kept constant for 15-20 minutes.
[0038] The ion source cleaning in step S3 is intended to effectively clean and activate the substrate surface through high-energy ion bombardment, optimize the surface comprehensive properties, promote uniform and dense deposition of the film layer, and thus improve the overall performance and long-term stability of the coating. In one example, in step S3, when the vacuum degree reaches (1.0-2.0)×10 -3 Pa, start the ion source of the vacuum coating machine, and set the ion cleaning parameters of the ion source as follows: neutralization current 0.6A, neutralization gas flow 8sccm, anode voltage 220V, anode current 2A, argon flow in neutralization gas 100%, and cleaning time 250-350s.
[0039] In step S4, in one example, during the coating process, argon gas is filled into the cavity of the coating machine and evacuated to form a flowing vacuum, ensuring that the vacuum degree of the coating is maintained at (4.5-5.5)×10 -3 Pa, and maintain the coating temperature at 150°C.
[0040] In step S4, in one example, the evaporation mode of the film material is: Ge, Al2O3 and Y2O3 are evaporated using electron beam heating, and YF3 is evaporated using resistance heating.
[0041] In step S4, in one example, the deposition rate of the film material is: the deposition rate of the Ge film layer is The deposition rate of the YF3 film is The deposition rates of Al2O3 and Y2O3 films are
[0042] In step S4, in one example,
[0043] The thickness of the first Ge film layer is 30nm.
[0044] The thickness of the second Al2O3 film is 305.48nm.
[0045] The thickness of the third Ge film layer is 40.19nm.
[0046] The thickness of the fourth Al2O3 film layer is 54.40nm.
[0047] The thickness of the fifth YF3 film layer is 691.87nm.
[0048] The thickness of the sixth Y2O3 film layer is 20 nm.
[0049] In step S4, for example, the film thickness is monitored using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller using a crystal oscillator method. After the ion source is cleaned, the crystal controller controls a new crystal oscillator of the plurality of crystal oscillators to work correspondingly, and the crystal oscillator frequency is 6 MHz.
[0050] In step S4, in one example, the ion source parameters when depositing the Ge film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 80V, anode current 0.7A, and the flow rate of argon in the neutralization gas is 100%; the ion source parameters when depositing the Al2O3 film layer and the Y2O3 film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1.0A, and the flow rate of argon in the neutralization gas is 100%; the ion source parameters when depositing the YF3 film layer are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 130V, anode current 1.3A, the flow rate of argon in the neutralization gas is 30%, and the flow rate of oxygen in the neutralization gas is 70%.
[0051] In step S5, in one example, after the plating is completed, the chamber is kept at a constant temperature of 150° C. for 5-15 minutes;
[0052] In step S6, in one example, the door is opened to take out the items when the temperature drops below 100°C.
[0053] [test]
[0054] Example 1
[0055] The method for preparing the zinc sulfide-based infrared mid-wave antireflection film system of Example 1 comprises the following steps:
[0056] S1. Before plating, the accompanying plating sheet and the product used as the zinc sulfide substrate of the lens were cleaned and four film materials, Ge, Al2O3, YF3, and Y2O3, were prepared. The thickness of the accompanying plating sheet was 1.0 mm and was cleaned by ultrasonic cleaning. Ultrasonic cleaning was performed using an alumina polishing solution, followed by ultrasonic pure water cleaning. The alumina polishing solution used was a 0.1 μm polycrystalline diamond solution from Nanjing Henry Precision Optics Co., Ltd.
[0057] S2, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake and pre-melt the film material,
[0058] in,
[0059] Chengdu Siwork Vacuum Technology Co., Ltd. manufactures and sells vacuum coating machines with Hall ion sources.
[0060] The temperature of the coating machine cavity is set to 150℃.
[0061] When the vacuum reaches 4.0×10 -3 The film material is pre-melted at Pa. Ge film material, Al2O3 film material and YF3 film material are pre-melted, while Y2O3 film material is not pre-melted. Ge film material and Al2O3 film material are pre-melted by electron beam heating, and YF3 film material is pre-melted by resistance heating. After the film material is pre-melted,
[0062] The temperature of the coating machine cavity reaches 150℃ and is kept constant for 20 minutes;
[0063] S3, when the vacuum degree reaches 1.3×10 -3 When Pa, the ion source of the vacuum coating machine was started to clean the lens with the ion source. The ion cleaning parameters of the ion source were set as follows: neutralization current 0.6 A, neutralization gas flow rate 8 sccm, anode voltage 220 V, anode current 2 A, argon flow rate in neutralization gas 100%, and cleaning time 350 s.
[0064] S4, under vacuum conditions, the first Ge film layer, the second Al2O3 film layer, the third Ge film layer, the fourth Al2O3 film layer, the fifth YF3 film layer, and the sixth Y2O3 film layer are deposited on the first surface of the lens in sequence. The six film layers constitute a film system, and all six film layers are deposited using an ion source.
[0065] in,
[0066] During coating, argon is filled into the cavity of the coating machine and evacuated to form a flowing vacuum, ensuring that the vacuum degree of the coating is maintained at 5.0×10 -3 Pa, and maintain the coating temperature at 150°C;
[0067] The evaporation mode of the film materials is as follows: Ge, Al2O3 and Y2O3 are evaporated by electron beam heating, and YF3 is evaporated by resistance heating;
[0068] The deposition rate of the film material is: The deposition rate of the Ge film layer is The deposition rate of the YF3 film is The deposition rates of Al2O3 and Y2O3 films are
[0069] The thickness of the first Ge film layer is 30nm.
[0070] The thickness of the second Al2O3 film is 305.48nm.
[0071] The thickness of the third Ge film layer is 40.19nm.
[0072] The thickness of the fourth Al2O3 film layer is 54.40nm.
[0073] The thickness of the fifth YF3 film layer is 691.87nm.
[0074] The thickness of the sixth Y2O3 film layer is 20nm;
[0075] The ion source parameters for depositing the Ge film were as follows: neutralization current 0.5 A, neutralization gas flow rate 8 sccm, anode voltage 80 V, anode current 0.7 A, and argon flow rate in the neutralization gas was 100%;
[0076] The ion source parameters for depositing the Al2O3 and Y2O3 films were as follows: neutralization current 0.5 A, neutralization gas flow rate 8 sccm, anode voltage 100 V, anode current 1.0 A, and argon flow rate in the neutralization gas 100%;
[0077] The ion source parameters for depositing the YF3 film were as follows: neutralization current 0.6 A, neutralization gas flow rate 8 sccm, anode voltage 130 V, anode current 1.3 A, argon flow rate in neutralization gas 30%, and oxygen flow rate in neutralization gas 70%.
[0078] The crystal oscillator method uses the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller to monitor the film thickness. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators.
[0079] The crystal oscillator frequency is 6MHz;
[0080] S5, after plating is completed, the cavity is kept at a constant temperature of 150°C for 10 minutes;
[0081] S6, wait until the temperature drops to 100°C, open the door and take out the items;
[0082] S7, repeating steps S1 to S6 to coat the same coating system on the second surface of the lens.
[0083] Example 2
[0084] Except for the following differences, the rest are the same as Example 1:
[0085] In step S2, when the vacuum reaches 5.0×10 -3 The film material is pre-melted at Pa;
[0086] In step S3, when the vacuum degree reaches 2.0×10 -3 When Pa, the ion source of the vacuum coating machine is started, and the cleaning time is 250s;
[0087] In step S4, the vacuum degree of the coating is maintained at 5.5×10 -3 Pa;
[0088] In step S5, the temperature is maintained at a constant level for 15 minutes.
[0089] Example 3
[0090] Except for the following differences, the rest are the same as Example 1:
[0091] In step S2, when the vacuum reaches 3.0×10 -3 The film material is pre-melted at Pa;
[0092] In step S3, when the vacuum degree reaches 1.0×10 -3 When Pa, the ion source of the vacuum coating machine is started, and the cleaning time is 300s;
[0093] In step S4, the vacuum degree of the coating is maintained at 4.5×10 -3 Pa;
[0094] In step S5, the temperature is maintained at a constant level for 5 minutes.
[0095] Comparative Example 1
[0096] Except that all the film layers in step S4 are not assisted by the ion source, the rest are the same as in Example 1.
[0097] Comparative Example 2
[0098] Except that YF3 is replaced by ytterbium fluoride (YbF3) in step S1 and step S4, the rest is the same as in Example 1. That is, in Comparative Example 2, only YF3 is replaced by YbF3 in the film material, and the rest is the same as in Example 1.
[0099] Comparative Example 3
[0100] Except for eliminating Y2O3 in step S1 and step S4, the rest is the same as in Example 1. That is, in Comparative Example 3, the outermost layer of the film system on each surface does not contain Y2O3, and the film system on each surface has five layers.
[0101] Figure 2 The graph is a transmittance curve of the accompanying plate of Example 1 and the film coated on both sides in the 3-5μm band. Figure 2 It can be seen that the average transmittance of the accompanying plate of Example 1 together with the films plated on both sides in the 3-5 μm band is 98.1%, that is, above 98%.
[0102] The accompanying plating sheets of Examples 1-3 and Comparative Examples 1-3 and the film systems on both sides were tested as follows.
[0103] Water bubble test: The accompanying plating sheet and the film systems on both sides are subjected to a water bubble test with tap water for 24 hours to observe whether the film layers on each side fall off from the accompanying plating sheet or whether the film layers on each side are cracked.
[0104] Adhesion test: After the blister and salt spray tests with tap water are completed, manually apply 3M tape to each side of the lens and pull the tape in the opposite direction of the adhesive end to determine whether the film layer is pulled up.
[0105] Medium friction resistance test: Withstand a pressure of 4.9N and rub the rubber friction head wrapped with degreased cloth 50 times (25 times back and forth) to check whether there are any scratches or other damage marks. If there are no such marks, it is qualified; if there are marks, it is unqualified.
[0106] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, observe whether the film layers on each side of the accompanying plating sheet fall off or crack.
[0107] High temperature test: In high temperature, 85℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off or crack.
[0108] Low temperature test: In a low temperature box, at -40℃ for 48 hours, observe whether the film layers on each side of the accompanying plating sheet fall off or crack.
[0109] Salt spray test: neutral salt spray test for 24 hours to observe whether the film layers on each side of the accompanying plating sheet fall off or crack.
[0110] Table 1 shows the average transmittance of the accompanying coating sheets of Examples 1-3 and Comparative Examples 1-3 together with the films on both sides in the 3-5 μm band and the results of various tests.
[0111] Table 1 shows the average transmittance of the accompanying coating sheets of Examples 1-3 and Comparative Examples 1-3 together with the films on both sides in the 3-5 μm band and the results of various tests.
[0112]
[0113] The above detailed description is used to describe a number of exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein may be combined to form multiple additional combinations that are not shown for the sake of brevity.
Claims
1. A method for preparing a zinc sulfide-based infrared mid-wave antireflection film system, characterized in that: Including steps: S1, before plating, clean the accompanying plating sheet and products of the zinc sulfide substrate used as the lens, and prepare the four film materials of Ge, Al2O3, YF3 and Y2O3; S2, the cleaned lens is placed in the fixture, and the fixture with the lens is hung in the cavity of the coating machine, vacuumed and baked, and the film material is pre-melted; S3, ion source cleaning lens; S4, under vacuum conditions, sequentially depositing a first Ge film layer, a second Al2O3 film layer, a third Ge film layer, a fourth Al2O3 film layer, a fifth YF3 film layer, and a sixth Y2O3 film layer on the first surface of the lens, so that the six film layers constitute a film system, and all six film layers are deposited using an ion source assisted deposition; S5, constant temperature maintenance after plating; S6, cooling and picking up; S7, repeating steps S1 to S6 to coat the same coating system on the second surface of the lens.
2. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film according to claim 1, characterized in that: In step S1, ultrasonic cleaning is performed, wherein the ultrasonic cleaning is performed using an aluminum oxide polishing solution, followed by ultrasonic pure water cleaning, wherein the aluminum oxide polishing solution is a 0.1 μm polycrystalline diamond solution produced by Nanjing Henry Precision Optics Co., Ltd.; and / or In step S1 , the thickness of the accompanying plating sheet is 1.0 mm.
3. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film according to claim 1, characterized in that: In step S2, the coating machine is a vacuum coating machine with a Hall ion source manufactured and sold by Chengdu Siwork Vacuum Technology Co., Ltd.; and / or In step S2, the temperature of the coating machine chamber is set to 150°C, and when the vacuum reaches (3.0-5.0)×10 - 3 The film materials are pre-melted at Pa. Ge film materials, Al2O3 film materials and YF3 film materials are pre-melted, while Y2O3 film materials are not pre-melted. Ge film materials and Al2O3 film materials are pre-melted by electron beam heating, and YF3 film materials are pre-melted by resistance heating. After the film materials are pre-melted, the temperature of the cavity of the coating machine reaches 150℃ and is kept constant for 15-20 minutes.
4. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film according to claim 1, characterized in that: In step S3, When the vacuum degree reaches (1.0-2.0)×10 -3 Pa, start the ion source of the vacuum coating machine, The ion cleaning parameters of the ion source were set as follows: neutralization current 0.6 A, neutralization gas flow rate 8 sccm, anode voltage 220 V, anode current 2 A, argon flow rate in neutralization gas 100%, and cleaning time 250-350 s.
5. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film according to claim 1, characterized in that: In step S4, During coating, argon is filled into the cavity of the coating machine and evacuated to form a flowing vacuum, ensuring that the vacuum degree of the coating is maintained at (4.5-5.5)×10 -3 Pa, and maintain the coating temperature at 150°C.
6. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film system according to claim 1, characterized in that: In step S4, The evaporation mode of the film material is: Ge, Al2O3 and Y2O3 are evaporated by electron beam heating, and YF3 is evaporated by resistance heating.
7. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film according to claim 1, characterized in that: In step S4, The deposition rate of the film material is: The deposition rate of the Ge film layer is The deposition rate of the YF3 film is The deposition rates of Al2O3 and Y2O3 films are 8. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film according to claim 1, characterized in that: In step S4, The thickness of the first Ge film layer is 30nm. The thickness of the second Al2O3 film is 305.48nm. The thickness of the third Ge film layer is 40.19nm. The thickness of the fourth Al2O3 film layer is 54.40nm. The thickness of the fifth YF3 film layer is 691.87nm. The thickness of the sixth Y2O3 film layer is 20nm. In step S4, the film thickness is monitored using a crystal oscillator method using a corresponding crystal oscillator of a plurality of crystal oscillators of a crystal controller. After the ion source is cleaned, the crystal controller controls a new crystal oscillator of the plurality of crystal oscillators to work correspondingly, and the crystal oscillator frequency is 6 MHz.
9. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film system according to claim 1, characterized in that: In step S4, The ion source parameters for depositing the Ge film were as follows: neutralization current 0.5 A, neutralization gas flow rate 8 sccm, anode voltage 80 V, anode current 0.7 A, and argon flow rate in the neutralization gas was 100%; The ion source parameters for depositing the Al2O3 and Y2O3 films were as follows: neutralization current 0.5 A, neutralization gas flow rate 8 sccm, anode voltage 100 V, anode current 1.0 A, and argon flow rate in the neutralization gas 100%; The ion source parameters for depositing the YF3 film are: neutralization current 0.6 A, neutralization gas flow rate 8 sccm, anode voltage 130 V, anode current 1.3 A, argon flow rate in neutralization gas 30%, and oxygen flow rate in neutralization gas 70%.
10. The method for preparing a zinc sulfide-based mid-wave infrared antireflection film system according to claim 1, characterized in that: In step S5, after the plating is completed, the cavity is kept at a constant temperature of 150°C for 5-15 minutes; In step S6, the door is opened to take out the items when the temperature drops below 100°C.